Improving entomological surveillance by minimizing insect damage in traps - Hempy, Thomas; Cohnstaedt, Lee (My University, 2017)
In the United States, mosquito control is a multi-billion dollar a year business. Municipal, state, and federal mosquito control organizations use mosquito surveillance traps such as the CDC light trap to target insect population control measures and monitor for pathogens. Most surveillance uses mosquito traps with fans. However the mosquitoes in the traps can be damaged during collection and storage by the fan, dehydration, and during sorting. This research shows the best ways to prevent the mosquitoes from being damaged.